Impact of blood pressure changes in cerebral blood perfusion of patients with ischemic Moyamoya disease evaluated by SPECT. Issue 6 (June 2021) - Liming, Zhao; Weiliang, Sun; Jia, Jia; Hao, Liang; Yang, Liu; Ludtka, Christopher; Jahromi, Behnam Rezai; Goehre, Felix; Zemmar, Ajmal; Tianxiao, Li; Hernesniemi, Juha; Andrade-Barazarte, Hugo; et al.
Our aim was to determine the impact of targeted blood pressure modifications on cerebral blood flow in ischemic moyamoya disease patients assessed by single-photon emission computed tomography (SPECT). From March to September 2018, we prospectively collected data of 154 moyamoya disease patients and selected 40 patients with ischemic moyamoya disease. All patients underwent in-hospital blood pressure monitoring to determine the mean arterial pressure baseline values. The study cohort was subdivided into two subgroups: (1) Group A or relative high blood pressure (RHBP) with an induced mean arterial pressure 10–20% higher than baseline and (2) Group B or relative low blood pressure (RLBP) including patients with mean arterial pressure 10–20% lower than baseline. All patients underwent initial SPECT study on admission-day, and on the following day, every subgroup underwent a second SPECT study under their respective targeted blood pressure values. In general, RHBP patients showed an increment in perfusion of 10.13% (SD 2.94%), whereas RLBP patients showed a reduction of perfusion of 12.19% (SD 2.68%). Cerebral blood flow of moyamoya disease patients is susceptible to small blood pressure changes, and cerebral autoregulation might be affected due to short dynamic blood pressure modifications.